Pesantren’s Social Innovation in Driving Agriculture and Social Change in Village - Amongjati, Sri Anom; Kolopaking, Lala Mulyowibowo; Saharuddin, Saharuddin (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
Pesantren are educational institutions that have strong social ties in local communities and some of them implement entrepreneurial activities in the agricultural sector. Therefore Pesantren have a big capacity as an agricultural movers and produce social innovation with the rural community. In the process of social change in the village, pesantren have the capacity in producing agents of change that encourage social innovation in the agricultural sector. This study aims to analyze the capacity of pesantren as an agricultural movers and create a new agricultural innovators in the process of social change in the village. The results of this study indicate that in the process of social change in the village, pesantren can accelerate social change in the village through the activities of social innovation in agriculture. In addition, the process of education activity by pesantren is able to create an graduate who are also new innovators in the community. In conclusion, pesantren are able to become agricultural movers and creator rural agents of change.